2013
DOI: 10.1179/2046905513y.0000000056
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ satisfaction with repair of paediatric cleft lip/cleft palate in Honduras

Abstract: Despite unmet expectations, parents of children who received medical mission surgery for cleft lip or cleft palate express satisfaction with outcomes. Other factors are likely to influence expressions of satisfaction in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Also, the history-taking questions, the physical examination, the administration of diagnostic tests, the prescription of medications, the referral to physician specialists, the delivery of answers to the patient’s symptoms, and the way this information is communicated are all areas where patients experience unmet expectations (Bell, Kravitz, Thom, Krupat, & Azari, 2002; Peck et al, 2004). Finally, once the patient has undergone a medical procedure or taken a prescription and they still do not feel better, or fully healed from their situation, unmet expectations are sometimes reported (Rivera, Hexem, Womer, Vinelli, & Feudtner, 2013). In the health care setting, unmet expectations can create a sense of diminished control for the patient (DeLuca & Lobel, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also, the history-taking questions, the physical examination, the administration of diagnostic tests, the prescription of medications, the referral to physician specialists, the delivery of answers to the patient’s symptoms, and the way this information is communicated are all areas where patients experience unmet expectations (Bell, Kravitz, Thom, Krupat, & Azari, 2002; Peck et al, 2004). Finally, once the patient has undergone a medical procedure or taken a prescription and they still do not feel better, or fully healed from their situation, unmet expectations are sometimes reported (Rivera, Hexem, Womer, Vinelli, & Feudtner, 2013). In the health care setting, unmet expectations can create a sense of diminished control for the patient (DeLuca & Lobel, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Several studies in this review consistently report on follow-up, showing that substantial efforts are being made to improve the data output of missions 16 34 35 49–51 61 63. Ten studies reported significant follow-up lengths of more than 6 months and high numbers of patients returning for follow-up were shown 16 34 35 47 49 58 60–62 66. The majority of these missions were engaged in long-term partnerships.…”
Section: Discussionmentioning
confidence: 83%
“…Organisations were active in Africa, South-East Asia, Eastern Europe, and South and Central America. A typical mission team consisted of two or three plastic and/or maxillofacial surgeons, one or two anaesthetists, a mission coordinator, theatre nurse and one or two resident doctors, totalling 8 to 10 individuals for one single mission 32 33 37 46 47 50 51 54 58. Some teams were considerably larger, up to 40 individuals 36…”
Section: Resultsmentioning
confidence: 99%
“…15 Four years in, that number is now over 11 000. As this model carefully ties high clinical volume with academic interests, research done through Operation Smile local centers has resulted in over 25 publications, [16][17][18][19][20][21][22][23][24][25][26] with almost 20 coming from GC4 alone. 10,[13][14][15][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Operation Smile India spent 2 preliminary years studying the government, culture, and infrastructure of Assam to develop the successful model for sustainable care that is GC4.…”
Section: Research In a High-volume Cleft Centermentioning
confidence: 99%